Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.2147/clep.s12741
|View full text |Cite
|
Sign up to set email alerts
|

Oral complementary medicine and alternative practitioner use varies across chronic conditions and attitudes to risk

Abstract: ObjectivesTo determine whether chronic conditions and patient factors, such as risk perception and decision-making preferences, are associated with complementary medicine and alternative practitioner use in a representative longitudinal population cohort.Participants and settingAnalysis of data from Stage 2 of the North West Adelaide Health Study of 3161 adults who attended a study clinic visit in 2004–2006. The main outcome measures were the medications brought by participants to the study clinic visit, chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 28 publications
2
5
3
Order By: Relevance
“…In common with other studies, we found that those who consult CAM practitioners are likely to be women and to have higher levels of education. However, in contrast with other studies [12,17], we did not find that living in an area of higher socioeconomic status was related to higher use. We have also been able to show a differentiation in use with a decline in use with increasing age, with those over 80 years of age being the lowest users.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In common with other studies, we found that those who consult CAM practitioners are likely to be women and to have higher levels of education. However, in contrast with other studies [12,17], we did not find that living in an area of higher socioeconomic status was related to higher use. We have also been able to show a differentiation in use with a decline in use with increasing age, with those over 80 years of age being the lowest users.…”
Section: Discussioncontrasting
confidence: 99%
“…We have also been able to show a differentiation in use with a decline in use with increasing age, with those over 80 years of age being the lowest users. In contrast to the Adams study [17] where 3.1% of those over 65 years visited CAM practitioners over the past year, our NSA sample showed use by 10.1% of those aged between 60 and 69 years; and 7.2% of those aged between 70 and 79 years in the past 3 months. It was only in the group of those aged 80 and above that the rate of use fell to 2.6%.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Adams et al have shown differences in characteristics when comparing CAM users form different geographical areas [50] as well as when comparing those using oral complementary medicines and those using CAM practitioners [51]. Davis et al have found differences when comparing adults who used CAM for health promotion and adults who used CAM to treat illness [52].…”
Section: Typologies Of Cam Usersmentioning
confidence: 99%